2022
DOI: 10.3389/feart.2022.842955
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Pore Characteristics of the Lower Permian Shanxi Formation Transitional Facies Shale, Eastern Ordos Basin, North China

Abstract: The Lower Permian Shanxi Formation in the Eastern Ordos Basin is a set of transitional facies shale, and it is also a key target for shale gas exploration in China. Based on lithofacies classification by X-ray diffraction and kerogen type identification, nanoscale reservoir space, pore volume, pore size distribution, surface area, and fractal characterization were studied using comprehensive methods including N2 and CO2 adsorption, mercury injection capillary pressure, field emission-scanning electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Hysteresis loops were observed at the relative pressure (P/P O ) of about 0.5 in the adsorption-desorption curves, signifying the presence of great differences in the pore size and pore morphology among shale samples that cause such adsorption behaviors at this pressure. This relative pressure was set as the threshold to divide the samples into two groups (Wang et al, 2022). The first group with P/P O =0-0.5 is subjected to the monolayermultilayer adsorption process controlled by van der Waals force, while the second group with P/P O =0.5-1.0 experiences the capillary condensation adsorption process controlled by surface tension (Sun et al, 2015;Wang et al, 2015).…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Hysteresis loops were observed at the relative pressure (P/P O ) of about 0.5 in the adsorption-desorption curves, signifying the presence of great differences in the pore size and pore morphology among shale samples that cause such adsorption behaviors at this pressure. This relative pressure was set as the threshold to divide the samples into two groups (Wang et al, 2022). The first group with P/P O =0-0.5 is subjected to the monolayermultilayer adsorption process controlled by van der Waals force, while the second group with P/P O =0.5-1.0 experiences the capillary condensation adsorption process controlled by surface tension (Sun et al, 2015;Wang et al, 2015).…”
Section: Geological Settingmentioning
confidence: 99%
“…However, the successful cases of shale gas exploration and development in China are limited to the Silurian marine shale in the Sichuan Basin and its surrounding areas (Zhang et al, 2019;Li, 2022;Li et al, 2022). With the advancement of exploration and development, alternative shale gas exploration targets need to be found Sun et al, 2022;Wang et al, 2022). To date, studies on the exploration potential of lacustrine shale gas have been conducted in the Jurassic Da'anzhai Member of Sichuan Basin, Triassic Yanchang Formation in Ordos Basin, Shahejie Formation of Bohai Bay Basin, Cretaceous Shahai and Jiufotang Formation in Fuxin Basin, and the Cretaceous Qingshankou Formation of Songliao Basin (Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of pore structure studies have been carried out on marine shale and found that nanoscale pore structure is strongly affected by mineral composition and organic matter abundance (Li et al, 2016;Jia et al, 2020). However, due to the huge difference in sediment composition, mineral composition and organic matter abundance between transitional shale and marine shale (Jia et al, 2020;Wang et al, 2022), the previous results of marine shale cannot be directly applied to transitional shale. The existence of pore water in shale reservoir will affect the adsorption capacity and flow capacity of shale gas to a great extent, which brings some difficulties to the evaluation of gas reservoir resources and the prediction of productivity (Zhang et al, 2022a;Xi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies on transitional facies shale focus on the characteristics of shale gas reservoirs such as TOC content, mineral composition, pore type and gas content (Li et al, 2019). Meanwhile, many studies have been carried out on the sedimentary environment, sedimentary model and pore structure of transitional facies shale (Xi et al, 2017;Liu et al, 2018;Luo et al, 2018;Xi et al, 2018;Wang et al, 2022), but systematic studies on pore fluid of shale pore system is rare. In this study, the effective pore size distribution is determined by dividing the fluid types in the pores, and the systematic evaluation of the transitional shale pores in the study area is realized, which also provides a new idea for the effectiveness evaluation of transitional shale reservoirs.…”
Section: Introductionmentioning
confidence: 99%